Rights of Indonesian Migrant Workers' Children to Access Education at Sanggar Bimbingan Hulu Langat Malaysia - Hidayat, Taufiq; Asmaroini, Ambiro Puji; .Sunarto, Sunarto; Sulton, Sulton; Chaniago, Zamawi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Human rights are fundamentally crucial to every individual, especially the right to education, which has also been stipulated in the Indonesian constitution following the international agreements. This research aims to obtain information about what causes the Indonesian migrant workers in Malaysia to have undocumented status, what problems they face in sending their children to a school, and what efforts and solutions can be made to obtain education for them. Through qualitative methods and a systematic approach, the researchers used various methods to gather data, such as interviews, observations, and documentation. This research found that the undocumented Indonesian migrant workers whose children lack proper documentation, let alone as they had entered Malaysia illegally, have no valid work or residence permission (overstaying), and got married in Malaysia to another foreign citizen. There were problems with their right to send their children to school, so the Sanggar Bimbingan Hulu Langat was established to overcome the problems and help the children get an education in Malaysia. The agenda turned out to be a means of resolving the issues that Indonesian migrant workers' children face so that they were able to access educational rights.